Determinants of Female Students’ Choice of STEM Programmes in Tertiary Education: Evidence from Senior High Schools in Ghana - Quansah, Frank; Sey, Vera Rosemary Ankoma-; Dankyi, Lydia Aframea (American Journal of Education and Learning, 2020)
This study examined the determinants of Senior High School (SHS) female students’ choice of STEM programmes in tertiary education in Ghana. Specifically, the study aimed at exploring: (a) school-related factors, (b) home-related factors, and (c) person-related factors which influence female SHS students’ choice of STEM programmes in tertiary education in Ghana. The study was grounded in the positivist’s paradigm. A cross-sectional survey design was used as the research design. The study was targeted to final-year female students in SHSs in three regions in Ghana. Single-sex male SHSs were excluded because only female students participated in the study. Through a multi-stage sampling procedure, questionnaires were administered to 1,938 final-year female students in 15 SHSs. Prior to the data collection, the questionnaire was validated using Response Factor Analysis (RFA) and Kuder-Richardson reliability estimate. Binary logistic regression with 1,000 bootstrap samples was used to analyse the data. The study revealed that school-related factors, such as the course of study, elective mathematics status, and interest in mathematics and science, influenced female students’ choice of STEM programmes in tertiary education. Home factors (e.g., education level of parents, socioeconomic status) and personal factors (e.g., self-confidence, career indecision, having a role model in STEM, locus of control) were also found to play a significant role in female students’ choice of STEM programmes in their tertiary education. Conclusions and recommendations were made based on the findings of the study.